Selection of upland rice lines in advanced yield trials and response to abiotic stress - Arif Tirtana; Bambang Sapta Purwoko; ISWARI SARASWATI DEWI; Trikoesoemaningtyas Trikoesoemaningtyas (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Tirtana A, Purwoko BP, Dewi IS, Trikoesoemaningtyas. 2021. Selection of upland rice lines in advanced yield trials and response to abiotic stress. Biodiversitas 22: 4694-4703. Breeding programs to obtain superior upland rice varieties with high productivity and adaptive in dryland must be prioritized to maximize the potential of dryland. This research aimed to obtain information on the agronomic performance of upland rice lines in advanced yield trials and select the best lines with high productivity and tolerance to drought stress and aluminum toxicity. Advanced yield trials were conducted from November 2016 until March 2017 in Bogor and Sukabumi using a randomized complete block design, where three replications were nested in the environments. Aluminum and drought stress evaluations were conducted at Muara Research Station, Bogor, in May-June 2018 and September-October 2018. Based on the selection index, twelve lines were selected with superior agronomic characters and high yield potential. These lines had characteristics as follows: days to harvesting (110.2-116.0 days), number of filled grains (70.6-101.3 grains), number of unfilled grains (27.9-58.4 grains), and productivity (2.2-2.9 tons ha-1). Evaluation of drought tolerance showed four lines with better drought tolerance than the drought-sensitive check IR20. The aluminum tolerance evaluation obtained two tolerant lines and nine lines with moderate responses to aluminum toxicity. The selected lines need to be further evaluated in multilocation trials.